Investigating the effects of microstructure and magnetic susceptibility in MRI - Cronin, Matthew John (2016)
Over the last decade, phase measurements derived from gradient echo MRI have increasingly been used as a source of quantitative information, allowing tissue composition and microstructure to be probed in vivo and opening up many new avenues of research. However, the non-local nature of phase contrast and the complexity of the underlying sources of phase variation mean that care must be taken in the interpretation and exploitation of phase information. The work described in this thesis explores the application of phase-based quantitative susceptibility measurements in vivo, and uses theory, experiment, and simulation to investigate the contribution of local structural effects to measurements of MRI signal phase.